Case report: Analysis of a case of hydrogen sulfide poisoning in a waste treatment plant - Genjiafu, Aerbusili; Shi, Mengdi; Zhang, Xiangxing; Jian, Xiangdong (Frontiers in Public Health, 2023)
This paper summarizes and analyzes the clinical data of a patient with Occupational hydrogen sulfide poisoning admitted to our hospital on March 4, 2023. On the morning of March 2, 2023, the patient worked at an environmental energy company (waste treatment plant) in Shandong Province for the first time, The job was to flush the sludge from the walls of the sludge treatment tank (anaerobic tank) with a water gun, which can release hydrogen sulfide gas. When the patient was about to start work after entering the tank for about 1 min, he suddenly smelled a harsh and pungent odor, felt dizzy and weak, and then the patient suddenly fainted. After hearing the sound of the patient fainting, the workman waiting at the entrance of the tank immediately called someone to go into the tank and quickly pull the patient out, and sent to the local hospital. In the local hospital, the patient was confused, accompanied by irritability, convulsion and other manifestations, and was treated with sedation and nutritional support. Two days later, the patient’s condition did not improve. For further diagnosis and treatment, the patient was transferred to the Department of Poisoning and Occupational Diseases in our hospital. After comprehensive treatment in our hospital, the patient got better and was discharged. Subsequent reexamination and follow-up showed that the patient recovered well. The work unit of the patient did not provide any personal protective equipment. According to the field investigation after the accident, the pipeline around the sludge treatment tank was blocked by sludge, resulting in a large amount of high concentration of H2S accumulated in the tank, causing the patient to faint soon after entering the tank, and his worker should be in the tank for a short time, and no health abnormalities were found. Hydrogen sulfide has a strong irritation to the human body, which can lead to asphyxia or even death in severe cases. The safety prevention and prevention knowledge of hydrogen sulfide poisoning should be popularized among enterprises and workers to reduce the occurrence of such incidents.